Effect of landfill leachate on germination of lettuce seeds (Lactuca sativa L.) - Franco, Heider Alves; Marques, Monica Regina da Costa; Braga, Clarisse Ferreira; Izidorio, Allana de Souza; Thode Filho, Sérgio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The constant changes in the relation of consumption increased solid waste generation. Associated to this is the formation of leachate that accumulate in landfills, presenting as an effluent with high polluting potential. The physico-chemical analyzes allow to identify and quantify the elements present. However, it is also important to carry out ecotoxicological tests to understand the relationship with the environment. Germination assays with lettuce (Lactuca sativa L.) submitted to different dosages of landfill leachate (3.125%, 6.25%, 12.5%, 25%, 50% and 100%) were proposed in two substrates: filter paper and soil. The objective of this work was evaluate the direct and indirect impact of the leachate on the germination of lettuce seeds, through determination of the LC50 and the values of NOEC and LOEC. In both trials it was not possible to determine the LC50 from the doses tested. The filter paper test showed to be more restrictive asthe determination of LOEC-0 occurred with the treatment of 3.125%. For the soil test the results are more flexible, the LOEC value is obtained with the 25% dose. The physiological behavior of the lettuce showed different relations from the introduction of the pollutant, but mainly in relation to the substrate used for germination.